Perlindungan Hukum Terhadap Korban Perdagangan Orang Ditinjau Dari Perspektif Kriminologi - Adis Nevi Yuliani; Ayu Chairun Nisa (Jurnal Litigasi Amsir, 2023)
This research aims to be able to find out and analyze normatively the legal protection against trafficking in persons from a criminological perspective. As well as finding the factors that cause human trafficking and being able to provide solutions to overcome human trafficking through the participation of the community and government. The research method used is through a Criminology approach by analyzing social phenomena in society. The results of this research found that legal protection for victims of human trafficking is not yet optimal, where it was found that the rights of victims have not been properly protected legally.